(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
This article discusses the contents of 17 letters from Sultan Mansur Shah I, the Sultan of Terengganu, are preserved in the library of the School of Oriental and African Studies at the University of London with the reference number SOAS MS 40320. Written in Malay using Arabic script, these were sent between 1785 and 1794. The contents discussthe political history of Terengganu involving foreign relations with the Siamese and the British. The Siamese were a continuous threat to Terengganu, especially after the Siamese conquest of Patani in 1785. Therefore, Terengganu sought to establish diplomatic relations with the British East India Company to protect it from the Siamese invasion. However, the attempt was unsuccessful due to the East India Company’s principle of non-involvement in Malay affairs. In terms of economy, Terengganu had trade links with Palembang, which supplied pepper and tin, as well as with ports in Java and Borneo. Terengganu also had trade relations with China and India. The Sultan of Terengganu employed a royal merchant, Saudagar Nasruddin, to manage his trade. British ships were used to carry pilgrims to Mecca through ports in Pulau Pinang and India. The letters also discuss the lineage of Sultan Mansur Shah I, which closely links him to the Johor and Patani sultanates. The entire contents of these letters have helped to provide more detailed information on the politics and economy of the Terengganu sultanate in the late 18th century. Keywords: The Light Letters, Terengganu, Sultan Mansur Shah I, Malay seals